1996
DOI: 10.1159/000172398
|View full text |Cite
|
Sign up to set email alerts
|

Total Pancreatectomy and Subtotal Duodenopancreatectomy for the Management of Carcinoma of the Head of the Pancreas: An Institutional Experience and Evolving Trends

Abstract: This retrospective study includes 88 consecutive patients treated by surgical resection for adenocarcinoma of the head of the pancreas between January 1973 and December 1992. Initially in 1973 total pancreatectomy was the treatment of choice. Our policy changed after a review of 47 consecutive total pancreatectomies in 1986 which showed no benefit. From 1986 the Whipple procedure became our standard operation. In the following 41 patients, a Whipple procedure was performed in 19 patients, and a total pancreate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Reasons for such controversies lie mainly in the many differences between the various studies published during recent years. The most important differences concern standardization of the surgical approach, the extent of lymph node dissection, the decision to resect portal vein segments for suspected or proven tumor infiltration, the percentage of R0 resections and the application of additional adjuvant treatment modalities [8,9,18,[25][26][27][28][29]. Consequently, the first aim of our study was to standardize as many aspects as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for such controversies lie mainly in the many differences between the various studies published during recent years. The most important differences concern standardization of the surgical approach, the extent of lymph node dissection, the decision to resect portal vein segments for suspected or proven tumor infiltration, the percentage of R0 resections and the application of additional adjuvant treatment modalities [8,9,18,[25][26][27][28][29]. Consequently, the first aim of our study was to standardize as many aspects as possible.…”
Section: Discussionmentioning
confidence: 99%
“…The TP group with higher 5-OS than the PD group (14% vs 0%) 9. In contrast, two studies reported that 5-OS was higher in the PD group than in the TP group 45,46. Nevertheless, several studies suggested that long-term survival after TP was comparable to that of PD.…”
Section: Discussionmentioning
confidence: 90%
“…In total, 45 studies were included in the systematic review that reported the morbidity or mortality for TP ( Appendix Table ) 5,9,12,13,18,2866. A total of 15 studies focused on pancreatic cancer,9,12,13,19,28,29,34,35,43,4547,49,51,53 16 studies focused on malignant and benign pancreatic disease,18,32,36,48,50,52,5461,63,64 10 studies reported on PDAC,3033,4042,62,65,66 and 4 studies3739,44 focused on benign disease. In studies focusing on pancreatic cancer, the morbidity of TP ranged from 36.2% to 75.0% and mortality ranged from 4.0% to 26.9%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations